Effects of Immediate Dentin Sealing and Pulpal Pressure on Resin Cement Bond Strength and Nanoleakage - Santana, V. B.; Alexandre, R. S. de [UNESP]; Rodrigues, J. A.; Ely, C.; Reis, A. F. (Operative Dentistry Inc, 2016)
Objective: The object of this study was to evaluate the simulated pulpal pressure (SPP) and immediate dentin sealing technique (IDS) effects on the microtensile bond strength (mu TBS) and nanoleakage of interfaces produced by different luting agents. Methods and Materials: Two self-adhesive luting agents (RelyX Unicem [UC] and Clearfil SA Luting [SA]) and two conventional luting agents (Rely X ARC [RX] and Panavia F [PF]) were evaluated. Eighty human molars were divided in four groups according to luting agents. Each group was subdivided according to SPP (with or without) and dentin sealing (immediate or delayed) using Clearfil SE Bond (n=5). After IDS was performed, specimens were stored in water for seven days before luting procedures. Composite blocks were luted according to the manufacturers' instructions. One half of the specimens were subjected to 15 cm H2O of hydrostatic pressure for 24 hours before cementation procedures and continued for 24 hours afterward. Then, restored teeth were sectioned into beams and tested in tension. Two additional teeth per group were prepared for nanoleakage evaluation with scanning electron microscopy. Bond strength data were statistically analyzed by three-way analysis of variance and Tukey test. Results: mu TBS of RX decreased when it was subjected to SPP without IDS. However, in the same conditions, mu TBS of UC increased. The IDS prevented negative influence of SPP on mu TBS of RX and PF; however, a decrease in mu TBS of SA and UC was observed. Except for RX, IDS increased mu TBS for all resin cements. Conclusion: Independent of SPP, the IDS technique obtained higher mu TBS for PF, SA, and UC and did not influence RX mu TBS.